Efeito hipoalgésico da corrente alternada de média frequência em quilohertz (Aussie) em indivíduos saudáveis: ensaio clínico randomizado - Agripino, Mayara Ellen de Jesus (2017)
Studies report that alternating current is more effective in promoting analgesia than low frequency pulsed currents. However, the hypoalgesic potential and the clinical use of the medium frequency alternating current in kHz (Aussie) are based on hypothetical mechanisms of action. The present study aimed to investigate the hypoalgesic potential of the Aussie Current (AC) in healthy individuals. Eighty-one healthy subjects underwent electrostimulation by using kilohertz-frequency alternating current for 20 minutes and were randomized into three distinct groups (1 kHz, 4 kHz or placebo). Pressure pain threshold (PPT, algometry), conditioned pain modulation (CPM, ischemic pain in the contralateral upper limb and algometry), temporal summation (TS, algometry) were measured before and after intervention, the level of anxiety (STAI-T and STAI-E), in turn, was measured only at the pre-intervention. At the end of the protocol, subjects were questioned regarding the treatment they received and the comfort during the stimulation (numerical scale) and, similarly, investigators were questioned about their expectation related to subject’s allocation groups. These responses were recorded and used to test the adequacy of the masking procedure regarding the subject and the investigator. The level of anxiety evaluated did not a statistically significant difference between the groups, who received the active AC (1 kHz / 4kHz) or placebo, (p> 0.05). Regarding PPT, there was no statistically significant difference in the active AC 1 kHz, active 4 kHz and placebo groups at any of the moments evaluated. The active group AC 4 kHz presented a statistically significant reduction in the amplification of pain intensity, verified by the reduction of perceived pain intensity, in the tenth (p = 0.02), twentieth (p = 0.01) and thirtieth second (p = 0.001) in the TS test. The active group AC 1 kHz, in turn, presented significant reduction of pain intensity only at the end of the measurement (thirty-second, p = 0.01). In the evaluation of the CPM, there was no significant difference of the PPT, during induction of ischemia, in the AC active groups 4 kHz and active AC 1 kHz, before and after intervention (p> 0.05). However, in the placebo group there was a significant reduction in PPT, only during induced ischemia, both before and after intervention (p = 0.01). Thus, our study provides evidence that kilohertz-frequency AC current, especially when used with an equivalent 4 kHz frequency, presents hypoalgesic effect, having having possible inhibitory action in the Central Nervous System (CNS).